Deciphering the mind of the CEO: Is Artificial Intelligence a valuable investment in customer acquisition? - Maldonado-Canca, Luis; Cabrera-Sánchez, Juan Pedro; Molinillo-Jiménez, Sebastián (Taylor & Francis, 2025)
The implementation of Artificial Intelligence (AI) technology in the customer acquisition process is an emerging reality in the business realm. This study aims to explore the drivers and barriers that lead CEOs intention to use artificial intelligence (AI) for customer acquisition process Drawing on the technology adoption literature, this study explores empirically which factors influence the intention to use AI for customer acquisition strategies using data from a survey with the participation of 409 CEOs. The results reveal that for them organizational (performance expectancy, effort expectancy, facilitating conditions and perceived economic value) and microenvironmental aspects (social influence) are the most significant criteria for making the decision to adopt it, while personal (anxiety towards AI) and macroenvironmental aspects (green behavior) are not significant. Both factors, perceived economic value and facilitating conditions are the two major drivers for adopting AI to improve customer acquisition processes.
Keywords: Inteligencia artificial; Artificial Intelligence (AI); Marketing Processes; Customer Acquisition; Perceived Economic Value; Green Behavior; Anxiety towards AI; Adoption Intent